PHILANTHROPY OF ISLAMIC BANKING: A STRATEGY IN STRENGTHENING THE ECONOMIC GROWTH AND PROSPERITY - Binti Nur Asiyah; M. Ridlwan Nasir; Muhamad Ahsan (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2019)
Islamic banking has philanthropy values presented in zakat and other virtue funds as it aims at enhancing economic growth and prosperity. These philanthropy instruments are one of the differences between Islamic banks and conventional banks. However, the role of zakat and other funds in enhancing people’s welfare needs to be analyzed since the market share of Islamic banks is still growing slowly. This paper is intended to analyze the influence of zakat and the other virtue funds towards the realization of social welfare. In specific, this paper also intends to find a strategy for strengthening welfare through the role of philanthropy of Islamic banks. This study utilizes a quantitative approach that is analyzed using the Spearman correlation test. The results of the paper are: first, zakat has no significant correlation on welfare; second, other virtue funds have a significant correlation with welfare. The strategy proposed is to empower zakat collection agencies funds and establish channeling that link to Islamic banks so that the productive zakat allocation can be managed by Islamic bank customers.==============================================================================================Filantropi Perbankan Syariah: Suatu Strategi dalam Penguatan Pertumbuhan Ekonomi dan Kesejahteraan. Bank syariah memiliki nilai filantropi dalam zakat dan dana kebajikan lainnya dimana instrumen tersebut bertujuan untuk meningkatkan pertumbuhan ekonomi dan kemakmuran masyarakat. Instrumen ini merupakan salah satu yang membedakan antara bank konvensional dengan bank syariah. Akan tetapi, sejauhmana peran zakat dan instrumen filantropi dalam meningkatkan kesejahteraan masyarakat masih harus dianalisis lebih lanjut mengingat pertumbuhan market share dari bank syariah masih sangat rendah. Paper ini bertujuan untuk menganalisis pengaruh zakat dan dana kebajikan lainnya terhadap terwujudnya kesejahteraan masyarakat. Paper ini sekaligus bermaksud menemukan suatu strategi dalam penguatan kesejahteraan melalui peran sosial finance bank syariah. Paper ini ditulis dengan pendekatan kuantitatif yang dianalisis dengan spearman correlation test. Hasil kajian menunjukkan bahwa: pertama, zakat memiliki korelasi yang tidak signifikan terhadap kesejahteraan; kedua, dana kebajikan memiliki korelasi yang signifikan terhadap kesejahteraan. Adapun strategi penguatan yang perlu dilakukan adalah meningkatkan alokasi dana zakat kepada lembaga amil zakat dan membangun chaneling dengan bank syariah agar alokasi zakat produktif dapat dikelola oleh nasabah bank syariah.